PENGARUH PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA UD. ASRI KECAMATAN TOMA KABUPATEN NIAS SELATAN - Duha, Asrinawati (Universitas Nias Raya, 2024)
The purpose of this study was to determine the effect of service on customer satisfaction at UD. Asri Toma District, South Nias Regency. The type of research used is quantitative research. The data source used is primary data, with a population of all consumers who make purchases at UD. Asri Toma District, South Nias Regency. The sample used is a Non Probability sampling design using Incidental Sampling technique, because the population is not known with certainty, the number of samples in this study amounted to 35 people. The data collection technique is to distribute questionnaires to respondents, namely UD customers. Asri Toma District, South Nias Regency. The data analysis method used is simple regression analysis. The results of this study indicate that service variables have a significant effect on customer satisfaction. Research suggestions are (1) The need to recruit permanent employees around two people so that customers get excellent and maximum service. (2) UD. Asri must be more careful in providing the products that customers want or buy, especially in purchasing goods that are classified as large so that damaged goods do not reach customers. (3) The process of service and provision of goods desired by customers needs to be improved by adding resources such as employees and freight cars so that customers can make purchases effectively and efficiently.